Water Filtration Machine with Monitoring System for Aquades Production and Founding an Optimal Pre- treatment Filter Ratio Before Reverse Osmosis Membrane - Ahmad Fauzan Adziimaa; Muhamad Sultan Rasyiid (Journal of ICT Research and Applications, 2025)
The increasing demand for distilled water (Aquades) in pharmaceutical and medical applications contrasts sharply with the limited quality of municipal water supplies and the high operating costs of commercial Aquades procurement. At the same time, many small-scale facilities still lack integrated systems capable of meeting the Indonesian Ministry of Health standard (Permenkes RI No. 32/2017). Existing research on reverse osmosis (RO) systems largely focuses on membrane or filtration performance, with limited attention to real-time water-quality monitoring and systematic optimization of pre-treatment filters. This study develops an integrated filtration and monitoring system designed to ensure regulatory compliance while optimizing the composition of pre-treatment materials. The system combines silica sand, activated carbon, and zeolite pre-filters with RO, supported by six analog sensors that continuously monitor pH, turbidity, and Total Dissolved Solids before and after filtration. Validation results show high sensor accuracy, with 99.77% for TDS, 98.10% for pH, and 99.97% for turbidity. Among six tested filter compositions, the 25% silica sand-25% activated carbon-50% zeolite configuration achieves the highest average filtration efficiency of 88.96%. These findings demonstrate that optimized pre-treatment combined with real-time monitoring can significantly improve RO performance and support cost-effective Aquades production for medical use.